BAHASA TAMSIL HADIS DALAM KITAB RIYADUSH SHALIHIN: KAJIAN BAB MENJAGA SUNNAH-SUNNAH NABI SAW - Zakiar Zakiar (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2018)
This paper examines the hadiths of the hadith tradition in riyadush shalihin: the study of the guarding of the Sunnah of the Holy Prophet. The issues that are being studied are: What are the traditions of the Holy Prophet in the chapter to keep the Sunnah of the Holy Prophet in Riyadush Shalihin, how the quality and how the scholars understand it. This research is pure literature by using the method of criticism of hadith as a means of assessing the quality of the hadith. The maudu'i method and the textual and contextual interpretation techniques of the hadiths have ensured the quality is authentic, then understood. The approach used is normative and linguistic. The results of the study show that the qualities of the hadith in hadeeth in the book of riyadush shalihin: the study of the chapter keeping the sunnah-sunnah of the prophet saw is authentic, while from the point of understanding, the hadith that speaks is only the way the Prophet gave the teaching of targib and tarhib to Muslims all the time.